Ryzyko obrotu instrumentami pochodnymi wyzwaniem dla audytorów - Różańska, Ewa (The Risk of Using Derivatives Presents New Challenges to Auditors, 2005)
Despite the fact that in some entities, the use of derivatives has reduced important exposures to risk, in some others their inherent characteristics have resulted in increasing business risk. Derivatives are becoming more complex and their use is becoming more commonplace increasing audit risk and presenting new challenges to auditors. Audit risk is that the auditor gives an inappropriate audit opinion when the financial statements are materially misstated. Audit risk has three components: inherent risk, control risk and detection risk. The auditor must consider knowledge obtained about business and about the key financial risks in assessing the components of audit risk. The IAPS 1012 presents such a list of risks related to derivatives: markéi risk, credit risk, solvency risk, legal risk. Although the statement recognizes the existence of other possible classifications (combinations of these risks), it surprises the concise classification that it offers, when there are many more risks that auditor should keep in mind during his evaluation. To reduce the audit risk to an acceptable level the auditor must understand the principal types of risk related to derivatives, to which the entities may be exposed. The risk can even go further than what is indicated by the IAPS 1012. Internal risks and, in particular, operational risk must be considered. This article aims to highlight to auditors and to analyze main areas of derivative risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 285-292